DEVELOPMENT OF JUMPING IN 15-16 YEAR OLD VOLLEYBALL PLAYERS BASED ON THE APPLICATION OF EXERCISES AIMED AT LEVELING THE BODY AXIS. - Jiyemuratov Baxadir Sulaymanovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article reveals the possibilities of developing jumping ability in 15-16-year-old volleyball players based on the development and introduction into the training process of means aimed at balancing the body axis. Determination of the level of balance and assessment of the quality of balance management of athletes were carried out on the ST-150 MERA stable simulator. The effectiveness of applying the tasks developed for the three-directional block is confirmed by the results of the pedagogical experiment.